2001
DOI: 10.1097/00003246-200101000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Use of an optical fiber scope to confirm endotracheal tube placement in pediatric patients

Abstract: The use of a flexible optical fiber scope is an accurate, fast, and practical method to determine ETT placement in pediatric patients on mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…We compared the reliability of chest auscultation, pulse oximetry, capnography, and peak inspiratory pressure with the effectiveness of the Rapiscope in detecting bronchial intubation and found the latter superior, not mentioning the usefulness in detecting nonendobronchial movements of the tracheal tube as well (ie, it may also detect accidental extubation). The Rapiscope was previously used for the detection of the tracheal tube's tip position in both pediatric and adult intensive care patients and was found clinically useful and superior to chest auscultation [21,22], thus supporting our results. A recent study [23] also reported the usefulness of the Rapiscope in quickly diagnosing esophageal intubation.…”
Section: Discussionsupporting
confidence: 86%
“…We compared the reliability of chest auscultation, pulse oximetry, capnography, and peak inspiratory pressure with the effectiveness of the Rapiscope in detecting bronchial intubation and found the latter superior, not mentioning the usefulness in detecting nonendobronchial movements of the tracheal tube as well (ie, it may also detect accidental extubation). The Rapiscope was previously used for the detection of the tracheal tube's tip position in both pediatric and adult intensive care patients and was found clinically useful and superior to chest auscultation [21,22], thus supporting our results. A recent study [23] also reported the usefulness of the Rapiscope in quickly diagnosing esophageal intubation.…”
Section: Discussionsupporting
confidence: 86%
“…Other commonly used formulas or methods for ETT placement should be validated in the context of EIT measure- ments. Additionally, EIT should also be compared with other approaches for verification of correct ETT placement; flexible fibreoptic bronchoscopy, [10][11][12] or ultrasound imaging of diaphragm motion. 13,14 In conclusion, this study demonstrates that EIT enables non-invasive recognition of correct ETT placement.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,9 Some anaesthesiologists predict appropriate depth of ETT placement using deliberate endobronchial mainstem intubation followed by withdrawal of the ETT 2 cm above the carina. 4 Alternative techniques that have been proposed to verify the correct position of the ETT include chest radiography, 4,7,9 flexible fibreoptic bronchoscopy, [10][11][12] ultrasound imaging of diaphragm motion, 13,14 ultrasound imaging of movement of the chest wall visceroparietal pleural interface, 15 and display of left and right lung sounds with a visual stethoscope technique. 16 Electrical impedance tomography (EIT) is a noninvasive monitoring method that generates crosssectional images of the chest organs based on the analysis of transthoracic electrical conductivity.…”
mentioning
confidence: 99%
“…The FOB was then withdrawn until the ETT tip was visualized, and a second mark was made on the FOB. The distance between these two marks on the FOB corresponded to the distance from the tip to the carina (T-C) (2,6). After measuring the T-C in the neutral position, the changes in this distance were measured after full flexion and full extension of the neck.…”
Section: Methodsmentioning
confidence: 99%
“…Both chest fluoroscopy and bronchoscopic evaluations can be applied effectively to verify the position and depth of the ETT (2,3). However, fluoroscopy is time-consuming, and the carina cannot always be easily located.…”
mentioning
confidence: 99%